Nurcholis Majid's Study of Thought for the Civilization of Science: A Critical Reflection on the Basic Values of Struggle in the Context of Islam and Indonesianness - Khoirul Amri Rambe; Siti Fatimah (LANGGAM: International Journal of Social Science Education, Art and Culture, 2026)
Nurcholish Madjid (Cak Nur) is a central figure in the renewal of Indonesian Islamic thought whose legacy continues to be a vital reference in contemporary national discourse. This paper aims to critically analyze Nurcholish Madjid's intellectual project in his quest to build a "civilization of knowledge" by tracing its roots to the Basic Values of Struggle (NDP). Through a qualitative analysis method with a thought study approach based on Cak Nur's primary works, this study shows that NDP serves as an epistemological foundation for all Cak Nur's renewal ideas. The principle of monotheism in the NDP is not only interpreted theologically, but also interpreted as the liberating power of reason from the sanctification of worldly entities such as tradition, power, and even science itself that paves the way for dynamic rationality and scientific objectivity. Key findings suggest that this NDP framework is actualized in two key interrelated contexts. First, in the context of Islam, it is manifested through the idea of modernism, "secularization" (desacralization) that distinguishes between the sacred and profane realms to foster critical reason, and inclusive pluralism as an ethical prerequisite for intellectual collaboration in a pluralistic society. Second, in the context of Indonesia, it is manifested through a theological justification for Pancasila, the concept of a participatory and civilized civil society as an incubator for the advancement of knowledge, and a modern and open vision of nationalism. The results of the analysis conclude that Nurcholish Madjid's thinking succeeded in presenting a coherent synthesis between the authenticity of Islamic teachings, the challenges of modernity, and the reality of Indonesia. His intellectual project offered a constructive middle ground, so that his intellectual legacy remains highly relevant as an alternative to the polarization between religious fundamentalism and liberal secularism. More than that, his thinking offers a solid philosophical foundation for building a productive dialogue between faith and science in an ever-evolving global society.